The Implementation of Extracurricular Scouting in the Development of Disciplinary Character in Terms of the Civic Dimension of Elementary School Students - Suratman Suratman; Suyitno Suyitno (Proceedings Series on Social Sciences & Humanities, 2023)
Character education in scouting is believed to be able to change current problems, especially disciplinary problems. This study aims to develop the disciplinary character of students in terms of the PKN dimension through the implementation of scouting extracurricular activities. The research method used is a qualitative research approach, with a descriptive qualitative design while the research subjects chosen are principals, scout coaches, learners. This study uses data collection techniques in the form of observation, interviews, documentation studies, data analysis carried out, namely data reduction, data presentation (data display), and conclusion drawing / verification to test the validity of data using credibility tests. The implementation of extracurricular scouting can develop the disciplinary character of learners. Increased implementation of extracurricular scouting to be carried out optimally so that the disciplinary character of students will increase.